2018
DOI: 10.1101/462317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BIN1 recovers tauopathy-induced long-term memory deficits in mice and interacts with Tau through Thr348 phosphorylation

Abstract: For molecular and cellular experiments in neurons and in human brain samples AbstractThe bridging integrator 1 gene (BIN1) is a major genetic risk factor for Alzheimer's disease (AD). In this report, we investigated how BIN1-dependent pathophysiological processes might be associated with Tau. We first generated a cohort of control and transgenic mice either overexpressing human MAPT (TgMAPT) or both human MAPT and BIN1 (TgMAPT;TgBIN1), which we followed-up from 3 to 15 months. In TgMAPT;TgBIN1 mice short-term … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
(78 reference statements)
2
9
0
Order By: Relevance
“…This observation is in line with decreased BIN1 isoform 1 protein expression in the AD brain compared with controls (our own results; Glennon et al, 2013). This would be also in agreement with the observation that an overexpression of the BIN1 isoform 1 may be protective in a model of Tauopathy (Sartori et al, 2019).…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 90%
“…This observation is in line with decreased BIN1 isoform 1 protein expression in the AD brain compared with controls (our own results; Glennon et al, 2013). This would be also in agreement with the observation that an overexpression of the BIN1 isoform 1 may be protective in a model of Tauopathy (Sartori et al, 2019).…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 90%
“…In addition, a functional risk variant of BIN1 has been associated with Tau loads (but not Aβ loads) in AD brains [18]. Furthermore, human BIN1 directly binds Tau and this interaction in neurons depends on the level of BIN1 expression, as well as the phosphorylation statuses of both BIN1 and Tau [85, 89, 110, 124]. Moreover, human BIN1 overexpression in a mouse model of tauopathy has been shown to increase BIN1–Tau interaction in the neuronal network and to rescue long-term memory deficits and Tau somatic inclusions induced by human Tau overexpression [110].…”
Section: Beyond Aβ Peptides and The App Metabolismmentioning
confidence: 99%
“…Tau's proline-rich domain binds directly to BIN1's SH3 domain and phosphorylation of Tau regulates this binding (47), highlighting a potential role for the Tau-BIN1 interaction in Tau-mediated AD deficits. A recent report used Tau-BIN1 PLA to identify modulators of Tau-BIN1 interaction (48) and found that phosphorylation of BIN1 modulates the interaction and that there is altered BIN1 phosphorylation in AD brain.…”
Section: Discussionmentioning
confidence: 99%